Section VI Industries and Minerals Draft Seventh Five Year Plan Andhra Pradesh 1985-90 Volume II - Planning Commission (Planning Commission, 1985)
Andhra Pradesh, though endowed with rich natural, mineral and agro-resources, paradoxically had remained an essentially Agricultural State without any appreciable industrial development. Despite the sustained investments and efforts made for the accelerated industrial growth, no major changes in the positive direction have been accomplished, in basic structural fabric of State’s economy. The fatalities of the situation are that, all the vital parameters governing the economic growth do cause grave concern and warrant a sense of introspection about the way in which we have been going about in determining our priorities in relation to the pressing needs and genuine aspirations of the masses.
Finance and Planning (Plg. Wing) Department
Government of Andhra Pradesh